First record of Phyllolabis savtshenkoi (Diptera, Limoniidae) in Morocco - Abdelkhaleq Fouzi Taybi; Youness Mabrouki; Lujza Keresztes (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2021)
In this paper, we provide the first record of Phyllolabis savtshenkoi in Morocco previously known only from Spain and the Canary Islands. In addition, Dicranomyia goritiensis and Geranomyia caloptera are recorded for the first time in the oriental region of Morocco.